The Strategy of Agroindustry Development of Teng-Teng Apel (A Case Study on Hilwa Nusantara Shop in Batu City) - Ummu Nadhiroh Islamiah; Mubarokah; Nisa Hafi Idhoh Fitriana (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
This study is conducted by purpose of identifying company environment and analyzing the strategy for agroindustry development of Teng-Teng Apel (cake made from apple fruit) in Hilwa Nusantara Shop in Batu City. The methods of data analysis used in this study are internal and external company analysis, Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE), SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM) analysis. The results of the study have showed that SWOT analysis indicates IFAS score 2.84 and EFAS value 2.94. Moreover, agroindustry position of Teng-Teng Apel of Hilwa Nusantara Shop is at Quadrant One (I). Based on company position, there are three alternative strategies, 1. To increase production capacity and quality using technology, 2. To extend market in developing sales volume, and 3. To maintain relationship and trust with raw material suppliers. First becomes first priority for Hilwa Nusantara with TAS value 5.49.